Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let M be the squares space $(R\times Z) \cup (Z\times R)$ covering the 8 space (pointwise union of two circles) by calling one circle of the 8 (path starting and ending at the dot of intersection of the two circles) x and the other y, and declaring each path from one dot to the one right to it as covering x and each path from one dot to the one above it as covering y. Call the cover map p and let there be $p_*:\pi(M_1)\rightarrow\pi_1(8) : \varphi\mapsto p\circ\varphi$. Show that $J=p_*(\pi_1(M))$ Is the commutator subgroup of $\pi_1(8)=F_2$. I have shown that the commutator subgroup is contained in J but I am struggling with the other direction. I have many ideas:

  • I know that $AutM=Z^2=F2/F2'=N(J)/J=F2/J$, but I'm not sure that from this follows that $J=F2'$.
  • I have discovered that $J=\{x^{i_1}y^{j1}x^{i_2}...| \sum i_k=\sum j_k=0\}$, from which it is obvious that $F2' \subseteq J$ But I am not sure how to show the other way. Wikipedia says the commutator subgroup can be thought of as a group of $g_1...g_n$ such that by rearranging the g's we get the identity, which means I'm right, I just don't know how to prove it.
  • I have shown manually that simple pathes are commutators (using the fact that a loop around each square is a commuator) but this proof failes for complex, self-intersecting paths.

Help will be appreciated.

share|cite|improve this question
up vote 1 down vote accepted

Let $s : F_2 \to F_2/F_2'$. Since $F_2' \subseteq J \subseteq F_2$, $s(J) = J/F_2'$ is a subgroup of $F_2/F_2'$, which is abelian. Now, since $J = \{x^{i_1}y^{j_1}x^{i_2}\ldots \}$ where $\sum i_k = \sum j_k = 0$, $s(J) = \{s(x)^{i_1}s(y)^{j_1}s(x)^{i_2}\ldots \}$. Since $F_2/F_2'$ is abelian, $s(J) = \{s(x)^{i_1}s(x)^{i_2} \ldots s(y)^{j_1}s(y)^{j_2}\ldots\} = \{s(x)^{i_1+i_2+\ldots} s(y)^{j_1+j_2+ \ldots} \} = \{s(x)^0 s(y)^0 \} = \{1\}$.

You can also show more straightforwardly, how $x^{i_1}y^{j_1}x^{i_2}\ldots = (x^{i_1}y^{j_1}x^{-i_1}y^{-j_1})(y^{j_1}x^{i_1+i_2}y^{-j_1}x^{-i_1-i_2})(x^{i_1+i_2}y^{j_1+j_2}x^{-i_1+i_2}y^{-j_1+j_2}) \ldots$ with some leftover at the end $x^{\sum i_k}y^{\sum j_k}$, or $y^{\sum j_k}x^{\sum i_k}$ depending on the parity of the length of the sequence. But if you pick a sequence in $J$, those leftovers are trivial, so there you have the explicit way to write your element in $J$ as a composition of commutators from $F_2$

And thus $J = F_2'$

share|cite|improve this answer
The first solution uses algebra not at all straightforward for me, though I understood it eventually! Also, the second solution is just what I was looking for, apparently I just didn't try hard enough... Thank you very much! – Idan Jan 26 '13 at 18:03

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.